2009
DOI: 10.1002/qua.560120711
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic resonance and conformational energy calculations of repeat peptides of tropoelastin: Correlation of 1J(15N-1H) with nonplanarity of peptide moiety

Abstract: Conformational energy calculations and 'H and I3C nuclear magnetic resonance ( N M R ) studies in CDCI3 of a tripeptide. N-Ac-Glyl-L-Val2-Cly~-OMe. suggested the Occurrence of an I I -membered hydrogen-bonded ring, or y-turn conformation. The theoretical calculations indicated that the Conformation occurs when there is a distortion of the planarity of the peptide moiety. An I5N N M R study of thc tripeptide in CDCI3 was undertaken to see if these spectral parameters might correlate with deviations from planari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The peptide C 8 turn might exist in linear peptides in solvents of low polarity at very low concentration (to avoid intermolecular amide⋅⋅⋅amide NH⋅⋅⋅OC H bonds). In this connection, in 1977 Urry and co‐workers carried out conformational energy calculations on Ac‐ L ‐Val‐Gly‐OMe (Ac, acetyl; OMe, methoxy) incorporating the effect of solvent and an NMR spectroscopy study on the same terminally blocked dipeptide 41. Their results apparently suggest the co‐existence of the C 8 conformation with other turn structures in equilibrium mixtures in solvents such as CCl 4 and CDCl 3 .…”
Section: Literature Surveymentioning
confidence: 99%
“…The peptide C 8 turn might exist in linear peptides in solvents of low polarity at very low concentration (to avoid intermolecular amide⋅⋅⋅amide NH⋅⋅⋅OC H bonds). In this connection, in 1977 Urry and co‐workers carried out conformational energy calculations on Ac‐ L ‐Val‐Gly‐OMe (Ac, acetyl; OMe, methoxy) incorporating the effect of solvent and an NMR spectroscopy study on the same terminally blocked dipeptide 41. Their results apparently suggest the co‐existence of the C 8 conformation with other turn structures in equilibrium mixtures in solvents such as CCl 4 and CDCl 3 .…”
Section: Literature Surveymentioning
confidence: 99%
“…A complete search for different patterns of intramolecularly hydrogen bonded conformations such as Cs and C7 conformations involving the N-H and C=O groups of the same or adjacent peptide unit or units [21], C,O or &turn conformations [22], as well as C11 or y turn conformations [23] was made during the conformational energy calculations. In principle the tripeptide can assume different types of P-turn conformations (see [22]) with a hydrogen bond between the Pro C=O and a carboxamide proton of the glycinamide, or y-turn conformations (see [23]) with a hydrogen bond between the Gly C=O and the proton attached to the Pro nitrogen atom. The results of this study have clearly demonstrated that the tripeptide cannot assume a y-turn conformation without significant deformation of the planarities of the peptide groups and out-of-plane bending of NH protons resulting in a pyramidal configuration at the nitrogen atoms [24].…”
Section: Introductionmentioning
confidence: 99%